(untitled) (Journal of the Bangladesh Agricultural University, 2026)
The freshwater climbing perch (Anabas testudineus) is highly valued in Bangladesh for economic significance and food source. Understanding the life-history traits of A. testudineus is crucial for developing effective long-term conservation and management. The present study provides a comprehensive analysis of life-history traits and biometric indices such as length-weight and length-length relationships (LWRs), and length-frequency distribution. A total of 102 specimens were collected between May and July 2025 using traditional fishing gears. Total length (TL), standard length (SL) and body weight (BW) were measured using digital slide calipers and an electronic balance. Total length of the specimens ranged from 6.96-13.49 cm and body weight varied from 9.59-35.07 g. The estimated ‘b’ values revealed a pattern of negative allometric growth (b<3.0). The LWR was highly significant (p<0.05) with r2 value 0.8632. The determined form factor, a3.0 was 0.00861, and Lm was 8.2383 ( 8.30) cm in TL. According to the findings of the study, the natural mortality, Mw was 1.26 year-1, with optimum age was 2.60 years and maximum life span, tmax was 9.65 years. The results will contribute to sustainable conservation and effective management of A. testudineus in Southwestern Bangladesh. J Bangladesh Agril Univ 24(2): 167–176, 2026